THE EFFECT OF SELF-REGULATED LEARNING AND DIGITAL LITERACY ON THE LEARNING OUTCOMES OF ECONOMICS SUBJECTS IN STUDENTS WITH SELF-EFFICACY AS AN INTERVENING VARIABLE - Adha, Adia Maritza (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The results of learning economics for students at SMA Negeri 4 Tangerang Selatan and SMA Negeri 8 Tangerang Selatan during the Covid-19 pandemic have changed. The implementation of online learning has an impact on students' confidence in learning strategies and digital literacy skills for the learning process. This study aims to determine the Effect of Self Regulated Learning and Digital Literacy on Learning Outcomes of Economic Subjects in Students with Self Efficacy as an Intervening Variable. This research is a quantitative study with samples in this study were class XI students at SMA Negeri 4 South Tangerang and SMA Negeri 8 South Tangerang with a total of 174 respondents. Data collection techniques for the distribution of questionnaires or questionnaires. The analysis method used in this study is path analysis with the SPSS version 25 program. The results of this study show that there is a positive and significant influence between self-regulated learning and digital literacy on economic learning outcomes through self-efficacy as an intervening variable.